Advanced endoscopy for the management of inflammatory digestive diseases: Review of the Japan Gastroenterological Endoscopy Society core session. Issue 4 (9th February 2022) - Matsuura, Minoru; Matsumoto, Takayuki; Naito, Yuji; Saitoh, Yusuke; Kanai, Takanori; Suzuki, Yasuo; Tanaka, Shinji; Ogata, Haruhiko; Hisamatsu, Tadakazu
Abstract : A series of workshops entitled "Advanced endoscopy in the management of inflammatory digestive disease" was held at the 97 th to 100 th biannual meeting of the Japan Gastroenterological Endoscopy Society. During these core sessions, research findings concerning various endoscopic practices in the field of inflammatory bowel disease (IBD) were presented, and meaningful discussions were shared on the evolving role and future challenges of endoscopy in IBD. This article reviews these core sessions and discusses current topics on the role of endoscopy, focusing on the diagnosis, disease monitoring, mucosal healing assessments, cancer surveillance, and therapeutic interventions in IBD.